Cultured People In The Millennial Era From A Christian Perspective And Their Red Threads In The Theological Documents Of The Batak Protestant Christian Church - Pintor Marihot Sitanggang (Jurnal Sosiologi Agama, 2025)
Humans will never be separated from their culture, and that is the basis for labeling cultured humans. Over time, the culture has developed, which has also received influence from the times. It is not surprising that in the current millennial era, many values ​​from culture have faded, or even experienced a transformation of meaning because they have to be adapted to the millennial era. Of course the study of theology, dogmatics, and practical ethics will not ignore the understanding of this reality. This article explains the Christian perspective on cultured humans in the millennial era. Used qualitative (literature) research methods, this article describe the Biblical basis of cultured humans from both the perspective of the Old Testament and the New Testament. This article develops Christian teachings on cultured humans in the context and millennial era through the perspectives of theologians, and then explains how the thread relates to the theological documents of the Huria Kristen Batak Protestant (HKBP) church in particular. Through this article, concrete contextualization from a Christian perspective on cultured humans in the millennial era will be clearly broken down, especially in the pluralistic Indonesian context.